Japanese Self-Image in Opposition to the Idea of Modern Europe and the Rise of Nationalism in Japan - Keiichi Kawate (Ksiegarnia Akademicka Publishing, 2020)
This paper attempts to explain the political and social context of the recent nationalistic trend in Japan in connection with the historical development of Japanese self-image. In Japanese modern history this self-image was formed in relation to modern Europe due to the fact that modern Japan first pursued the modernization of Europe and then tried to overtake it. The first goal of this paper is to provide an analysis of the formation process of Japanese self-image from a historical perspective. This process was divided in three phases which were connected with a changing understanding of Japanese modernity. It started with the criticism of the idea of European modernity in the 1940s and led, through the theory of modernization, to the development of the “theory of Japanese culture” (Nihonbunkaron) in the 1980s. The second goal of this paper is to conduct an analysis of the features of Japan’s society, economy, and politics since the 1990s. The links between the collapse of the “Bubble Economy” and a rise in nationalism are shown. Although the article focuses on the domestic issues of Japan, it also reflects Japanese understanding of modern Europe and contributes to the understanding of cultural exchange between Europe and Japan.